Specific Heat Behavior in the Kondo Lattice Model With Hybridization Interaction Under Low Temperature Regimes - I.S, Okunzuwa; Ejere, Arthur I. I; Amenaghawon, Oni-Ojo E.; Eddy, Aigbekaen E. (European Scientific Journal, ESJ, 2018)
A finite size analysis of the Kondo lattice model with hybridization interaction between localized and extended orbitals using the exact diagonalization technique has brought more insight into the specific heat behavior of the heavy fermion (HF) systems under low temperature regimes. The specific heat under the antiferromagnetic region of temperatures below 3k is lower than that of the ferromagnetic region. While the specific heat for temperatures above 4k, shows a reversed trend.